1983
DOI: 10.1172/jci111024
|View full text |Cite
|
Sign up to set email alerts
|

Reinitiation of sperm production in gonadotropin-suppressed normal men by administration of follicle-stimulating hormone

Abstract: A B S T R A C T The specific roles of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in controlling human spermatogenesis are poorly understood. We studied the effect of an experimentally induced, selective LH deficiency on sperm production in normal men. After a 3-mo control period, five men received 200 mg testosterone enanthate (T) i.m./wk to suppress LH, FSH, and sperm counts. Then, while continuing T at the same dosage, human FSH (hFSH) was administered simultaneously to replace FSH activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…After treatment with T, 200 mg im weekly, and the induction of oligoazoospermia, hCG (5000 IU im three times weekly) (2,4) or pituitary-derived LH (1100 IU sc daily) (17) was found to restore sperm concentration partially. In a similar study, suppression of serum LH and selective FSH replacement (100 IU sc daily) also partially restored sperm concentration (1). In such studies, the complete elimination of one or other gonadotropin cannot be assured, but such data support the contention that both FSH and LH/intratesticular androgens are needed for quantitatively normal spermatogenesis to occur.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…After treatment with T, 200 mg im weekly, and the induction of oligoazoospermia, hCG (5000 IU im three times weekly) (2,4) or pituitary-derived LH (1100 IU sc daily) (17) was found to restore sperm concentration partially. In a similar study, suppression of serum LH and selective FSH replacement (100 IU sc daily) also partially restored sperm concentration (1). In such studies, the complete elimination of one or other gonadotropin cannot be assured, but such data support the contention that both FSH and LH/intratesticular androgens are needed for quantitatively normal spermatogenesis to occur.…”
mentioning
confidence: 87%
“…I N MAN, BOTH gonadotropins are required to reinitiate and maintain quantitatively normal sperm production after experimentally induced oligoazoospermia (1)(2)(3)(4). However, the relative roles of FSH and LH/intratesticular androgens on germ cell development remain unclear.…”
mentioning
confidence: 99%
“…In this setting, the use of hCG, as an LH substitute, will partially restore spermatogenesis [85,86] as will FSH, but combined action of both will fully restore sperm output.…”
Section: Evidence For Requirements For Spermatogenesismentioning
confidence: 99%
“…Using hpg mice, which, due to the failure of GnRH secretion by the hypothalamus, have undetectable levels of FSH and LH, Singh et al (11) showed that spermatogenesis could be initiated and maintained by the use of high doses of exogenous T. Although the mice treated in this manner were fertile, their testes were smaller than those of normal controls, and the numbers of testicular spermatids were decreased. However, other studies using passive immunization against FSH (5) in the rat have supported a role for FSH during spermatogenesis.In the human, several studies have emphasized the importance of FSH in the stimulation of spermatogenesis in some men with hypogonadotropic hypogonadism as well in the restoration of spermatogenesis in normal men in whom spermatogenesis had been suppressed by testosterone treatment (12)(13)(14).In a more specific approach to the removal of FSH, Kumar et al (15) used targeted disruption of the gene encoding the ␤-subunit of FSH in mice. They showed that male mice were fertile, and spermatogenesis proceeded successfully to completion.…”
mentioning
confidence: 99%